The carbon conundrum: Hopes and hurdles in Indonesia’s OJK-led trading scheme - Dinda Keumala; Ahmad Sabirin; Nadia Nursantih; Elya Almadinatulmunawaroh; Anita Kadir (Jurnal Hukum Novelty, 2025)
Introduction to the Problem: Indonesia is one of the world's largest carbon emitters and has good potential for carbon trading. However, several aspects of carbon trading in Indonesia still need to be addressed, including difficulties in carbon value, carbon price setting, market monitoring, and carbon trading infrastructure development. Purpose/Objective Study: The research examines Indonesia’s carbon trading challenges and opportunities in the climate change era. Then, what is OJK's role in terms of carbon trading? Design/Methodology/Approach: The research methods used a normative study by looking at carbon emission trading regulations in Indonesia, as well as a systematic literature review involving researching, reading, analyzing, evaluating, and summarizing scholarly literature. Finding: The study reveals that OJK regulates carbon trading through frameworks like Law No. 4 of 2023 and OJK Regulation No. 14 of 2023, enabling carbon units to be traded as securities with a market potential of US$300 billion per year, supported by Indonesia's forests' carbon sequestration. Key challenges include developing carbon trading infrastructure, mastering emission reduction technologies, effective OJK market surveillance, and enhancing public engagement and transparency. Opportunities include economic growth from foreign investment, promoting sustainable development through renewable energy projects, and integrating with the global carbon market. OJK's role is crucial in regulating and supervising carbon trading, developing market infrastructure, ensuring compliance, building participant capacity, aligning with international standards, supporting climate change mitigation, and fostering international partnerships. Thus, OJK is essential for transparent, fair, and compliant carbon trading, addressing challenges, and leveraging opportunities, supporting Indonesia's net-zero emissions target by 2060 and global climate goals. Paper Type: Research Article